2003
DOI: 10.1161/01.hyp.0000085197.20043.44
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoexcitation by PVN-Injected Bicuculline Requires Activation of Excitatory Amino Acid Receptors

Abstract: Abstract-Acute blockade of ␥-aminobutyric acid (GABA)-A receptors in the hypothalamic paraventricular nucleus (PVN) increases mean arterial pressure (MAP), heart rate (HR), and sympathetic nerve activity (SNA). However, the underlying neural mechanisms have not been fully determined. We tested the hypothesis that responses to GABA-A receptor blockade in the PVN require activation of local ionotropic excitatory amino acid ( Key Words: heart failure Ⅲ hypertension, arterial Ⅲ sympathetic nervous system Ⅲ arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
100
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 26 publications
18
100
0
1
Order By: Relevance
“…Future studies will have to show how the SCN (via the sympathetic and parasympathetic branches of the ANS) controls the balance between glycogenolysis and glycogenesis. In this regard, glutamatergic SCN outputs might also be important (Csaki et al, 2000;Chen et al, 2003;Perreau-Lenz et al, 2004). Indeed, apart from GABA, glutamatergic (SCN) inputs to the PVN may also show a daily variation.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will have to show how the SCN (via the sympathetic and parasympathetic branches of the ANS) controls the balance between glycogenolysis and glycogenesis. In this regard, glutamatergic SCN outputs might also be important (Csaki et al, 2000;Chen et al, 2003;Perreau-Lenz et al, 2004). Indeed, apart from GABA, glutamatergic (SCN) inputs to the PVN may also show a daily variation.…”
Section: Discussionmentioning
confidence: 99%
“…14,16,26 Previous studies have shown that microinjection of the glutamate receptor antagonist alone into the PVN has little effect on the sympathetic output and arterial blood pressure in normotensive rats. 15,27 These data suggest that the glutamatergic input in the PVN is not critically involved in tonic control of sympathetic vasomotor tone in normotensive conditions. However, little is known about whether glutamatergic input in the PVN plays a role in the regulation of resting sympathetic outflow and blood pressure in hypertension.…”
mentioning
confidence: 88%
“…Electrode resistance was measured in vivo and averaged 25-35 M⍀. Electrodes were lowered vertically into the PVN at the following stereotaxic coordinates (in mm): Ϫ1.6 to Ϫ2.3 mm from bregma, 0.2-0.8 mm lateral to midline, and 7.2-mm ventral to the brain surface Toney 2001, 2003a,b;Chen et al 2003). The PVN was probed for single-unit activity by advancing the recording electrode in 2-m vertical steps with a piezoelectric micropositioner (EXFO-Burleigh, Quebec, Quebec, Canada).…”
Section: Extracellular Single-unit Recordingmentioning
confidence: 99%
“…In spite of receiving strong tonic inhibitory input (Chen and Toney 2003b;Chen et al 2003;Kenney et al 2003;Li et al 2006;Martin et al 1991), PVN neurons nevertheless do contribute to ongoing SNA. In anesthetized rats, for example, studies have shown that acute inhibition of PVN neuronal activity or blockade of excitatory inputs reduces ongoing renal SNA (RSNA) (Akine et al 2003;Allen 2002;Stocker et al 2004b, lumbar SNA , and ABP (Akine et al 2003;Allen 2002;Freeman and Brooks 2007;Stocker et al 2004b.…”
Section: Introductionmentioning
confidence: 99%